Preparation and in vitro Evaluation of Indomethacin Microspheres Prepared with Eudragit RS 100 and Eudragit RL 100 by Solvent Evaporation Method - N. Pal, Rabindra; Chakraborty, Manas; K. Gupta, Bijan; Debnath, Rabindra; Maity, Abhijit; Mazumder, Rana (Asian Journal of Chemistry, 2010)
The aim of the study is to prepare and evaluate Eudragit micro spheres containing indomethacin. Micro spheres were prepared by solvent evaporation method using acetone/liquid paraffin system. The influence of formulation factors (stirring speed, polymer: drug ratio, type of polymers, ratio of the combination of polymers) on particle size, encapsulation efficiency and in vitro release characteristics of micro spheres were investigated. The yield of preparation and the encapsulation efficiency were obtained. Mean particle size changed by changing concentration of the polymer: drug ratio or stirring speed of the system. Although indomethacin release rates from Eudragit RS micro spheres were very fast and incomplete for all formulation, drug release were very slow from micro spheres prepared with Eudragit RL100 only. When Eudragit RS 100 was added to Eudragit RL100 during preparation of micro spheres, release rates become controlled and achieved the release profile suitable for peroral administration.